The Ontology of Digital Transformation in the Perspective of Resource-Based Theory - Adi Munandir; Reza Ashari Nasution; Prawira Fajarindra Belgiawan; Aurik Gustomo (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
Digital transformation research lacks theoretical coherence while practitioners experience high failure rates, questioning the field's knowledge completeness. Given digital transformation's nature as a resource-driven process, this study assesses whether decade-long research has addressed all essential elements defined by resource-based theory. We constructed a conceptual blueprint incorporating resource-based theory's core principles, drawn from theoretical critiques, empirical validations, and extensions, to evaluate research comprehensiveness. Using systematic literature review and keyword analysis across 46 studies (2012-2024), we mapped digital transformation scholarship against our blueprint. Results show substantial coverage of environmental contexts and resource domains, yet reveal a critical gap in digital resource orchestration. Examination of 42 empirical studies confirms zero attention to orchestration concepts, highlighting knowledge deficiencies that may explain transformation failures. To address this limitation, we introduce a digital resources orchestration framework integrating resource-based and dynamic capabilities theories across two dimensions: content (aligning digital assets with transformation phase requirements) and mechanism (adaptive coordination via multi-organizational layers). This framework offers a holistic resource-based perspective on digital transformation, providing structured ontological mapping to direct future research toward resolving fundamental challenges and improving transformation outcomes.